Seeding solutions: Volume 1. Policy options for genetic resources - Crucible II Group (2000)
This volume brings readers up to date on what has changed, scientifically, politically and environmentally, since the first publication in 1994 of People, Plants and Patents, the book that summarized the major issues related to the owenership, conservation and exchange of plant germplasm. It offers policymakers a clear description of the facts, the fights and the fora relevant to genetic resources. Those new to these issues will also be offered a clear picture of why germplasm zis important and how it relates to trade negotiations, intellectual property disputes and national and international food and health security.